If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(x + -2) = 4x + 2 Reorder the terms: -1(-2 + x) = 4x + 2 (-2 * -1 + x * -1) = 4x + 2 (2 + -1x) = 4x + 2 Reorder the terms: 2 + -1x = 2 + 4x Add '-2' to each side of the equation. 2 + -2 + -1x = 2 + -2 + 4x Combine like terms: 2 + -2 = 0 0 + -1x = 2 + -2 + 4x -1x = 2 + -2 + 4x Combine like terms: 2 + -2 = 0 -1x = 0 + 4x -1x = 4x Solving -1x = 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -1x + -4x = 4x + -4x Combine like terms: -1x + -4x = -5x -5x = 4x + -4x Combine like terms: 4x + -4x = 0 -5x = 0 Divide each side by '-5'. x = 0 Simplifying x = 0
| Y-(-41)=108 | | x+5+2x=29 | | 9x^2+1=-15 | | 30(q+2)=990 | | -4(2w-8)=4-12w | | 1=3(g-14)-5 | | 1/6v=-7 | | 4(x-5)/2=? | | 67-5x=-75 | | 5(x)=20+3(x) | | 6r^2+6r-36=0 | | 7x+41+3x-1=180 | | 67-(-5x)=-75 | | 25(j+6)=750 | | .5x+3=2(x-2.5) | | -4(m+3)=23 | | 7r-2(6r-5)=20 | | N/-1=13 | | m+1.02=9 | | 7-x=-1+3x | | 10(h+35)=540 | | 1.75=0.2m | | 3(37+-8y)+2y=1 | | 5/v=11/13 | | f*s*h*d*n*c*m*x*gt*v*n*c*vg*n*d*x*j*xz*h*vc*5+58=9876543210 | | 170*3.65= | | -54=b-35 | | j-15j=-28 | | 2.50+0.50=1.00+75m | | 3x-24+2x= | | Z/6=19 | | 2r+3r+4r-6r=18 |